Initial conditions for nuclear collisions: theory overview - Mazeliauskas, Aleksas (Nuclear physics. A, Nuclear and hadronic physics, 2019)
We overview the current status and recent developments on initial conditions in ultra-relativistic nucleus-nucleus collisions. Specifically, we look at the progress in understanding the role of sub-nucleonic fluctuations in large and small collision systems. Next, we review the current ideas of going beyond boost invariant initial conditions and introducing physically motivated rapidity fluctuations at RHIC and LHC energies. Finally, we discuss the time evolution of initial stages and the matching between different descriptions of the QGP.
XXVIIth International Conference on Ultrarelativistic Nucleus-Nucleus Collisions (Quark Matter 2018)
Gesehen am 26.11.2019